(Post-)Industrial Narratives: Remembering Labour and Structural Change in Oral History - GARRUCCIO, ROBERTA (2016)
Although this is a workshop devoted to Oral History, my presentation will show a photo gallery. I will now explain why. The place represented is Sesto San Giovanni, a medium-sized city to the north of Milan that became the fifth industrial district in Italy during the XX century. Today Sesto epitomizes the local variety of the wider deindustrialisation processes that affect so many cities in the North-Atlantic, West-European area together with the post-Soviet world. The pictures show the ruins of its huge plants, opened at the beginning of the century and shut down before its end. The shots were taken by an amateur photographer who collaborated on an articulated research project. This project aimed to directly relate the photographic representation of a former industrial spaces in Sesto as they are today to the oral sources collected by the research group in a campaign of interviews carried out between 2013 and 2015. The interviews focused on the case of the Falck steel-making company. The Falck area is a vast redevelopment operation, one of the most important in Europe, and among the major real estate investments in Italy at the moment. The research, funded by the Lombardy Region, was born from the idea to enhance cultural memory in Sesto with the photo reportage as an important visual segment. The corporate wasteland is the object of the ever more frequent practice of organised urban exploration. It is presented as the modern Gothic (Edensor 2005) or as a new wilderness (High and Lewis 2007). Likewise, the photography of post-industrial areas arising from this kind of urban exploration seems to have become an iconographic genre of its own. Created by the ruins of manufacturing companies and their dismantling in Western world, this genre is dictating a new aesthetic of deindustrialisation. Some critics have stigmatised it as “ruin porn”, a derogative phrase that has already turned into an academic topos (High 2013; Apel 2015). My presentation intends to investigate how this emerging aesthetic is one with the ...